UJI KEPRAKTISAN PERANGKAT EKSPERIMEN ELASTISITAS MODULUS PUNTIR SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - Amelia Dwi Puspita; Yennita '; Zuhdi Ma’ruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research has a purpose to find out the practicality equipment of modulus rigidity and student worksheet as physic learning media for senior high school. The method that used is Research and Development (R&D) with Borg and Gall development model in test of introduction phase that usually called as practicality test. The subject are 20 student of XI Science and 3 teachers of physic in 5 Senior High School at Pekanbaru. In this research, the information analyzed descriptively with average score every aspect estimation practicality that obtained by changing inquiries. From it, the estimation of student  and teachers  can be known based Likert Scale. After that, decision of practicality test can be determined by distance of average score that very low, low, high, and very high.The result score average practicality for equipment experiment in the research  is 3,67             in category very high by teachers and 3,28 with in category high by student. And the result practicality student worksheet get it very high with average score 3,77 and 3,30 by teachers and student. Therefore, it can be concluded practicality of equipment modulus rigidity and student worksheet can defined practical as physic learning media for senior high school. Keywords: Modulus rigidity, practicality,equipment, student worksheet